Building Monastic Cloisters in the Iberian Peninsula (8th-11th centuries): Regular Layouts and Functional Organization - Boto Varela, Gerardo (Hortus Artium Medievalium, 2017)
Abstract As is well known, the cloisters of monasteries and cathedrals were being designed as quadrilaterals with porches and rooms arranged around the perimeter by the end of the eighth century. We know how they developed from philological (Fontanelle), documental (Sankt Gallen) and archaeological studies (Munstair, Lorsch or Fulda). The same formula was used in France throughout the 10th and 11th centuries, as is evidenced by the cloisters of Autun, Vezelay and Cluny II, which was originally made of wood until Odilo (994-1049) rebuilt it in marble. Recent findings at the Catalan monastery of Ripoll raise the possibility that full square cloisters were being built south of the Pyrenees before 1000. This cloister should be studied in relation to other Catalan enclosures such as Sant Cugat (beginning 11th c.) which had a stone portico from the outset, or the lower cloister at Sant Pere de Rodes. The morphology of these enclosures can be explained through comparison with other early Catalan examples. Nevertheless, the international literature has ignored the possibility that there were regular square or half square cloisters in the Iberian Peninsula from the Visigothic period onwards. It is possible that Carolingian proposals were not the only way of experimenting with quadrangle cloister layouts in both monasteries and cathedrals in Mediterranean Europe during the High Middle Ages.